2019
DOI: 10.1186/s13012-019-0924-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of removal and restriction of me-too medicines in a hospital drug formulary on in- and outpatient drug prescriptions: interrupted time series design with comparison group

Abstract: Background The study covered in- and out-of-hospital care in a region in north-western Spain. The intervention evaluated took the form of a change in the hospital drugs formulary. Before the intervention, the formulary contained four of the five low molecular weight heparins (LMWHs) marketed in Spain. The intervention consisted of withdrawing two LMWHs (bemiparin and dalteparin) from the formulary and restricting the use of another (tinzaparin), leaving only enoxaparin as an unrestricted prescript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 31 publications
4
16
1
Order By: Relevance
“…The out-of-hospital effects recorded in this new study would not appear to be as strong or as immediate as those observed in other therapeutic groups in the same settings with the same methodology (e.g., the case of low-molecular-weight heparins). 10 This agrees with a study that shows that the intensity of induction depends on the therapeutic drug class. 13 Our results also indicate that the inclusion of a new drug tends to have a more long-term effect, unlike withdrawal from the formulary, which seems to have a more immediate effect.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The out-of-hospital effects recorded in this new study would not appear to be as strong or as immediate as those observed in other therapeutic groups in the same settings with the same methodology (e.g., the case of low-molecular-weight heparins). 10 This agrees with a study that shows that the intensity of induction depends on the therapeutic drug class. 13 Our results also indicate that the inclusion of a new drug tends to have a more long-term effect, unlike withdrawal from the formulary, which seems to have a more immediate effect.…”
Section: Discussionsupporting
confidence: 91%
“…Trends in out-of-hospital desvenlafaxine and venlafaxine (defined daily doses per 1000 inhabitants per day [DDD/TID]) impact would be mitigated by large discounts from the pharmaceutical industry), 7,[9][10][11]35 but can also be transmitted to out-of-hospital costs (though in our case, these did not turn out to be statistically significant in the model with control group).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations